Urban spatial politics and collective action in revolutionary Cairo: Counter spaces and paradoxes of mobilisation. (October 2022) - Ismail, Salwa
Abstract: This article centres the role of Cairo's popular forces in the 2011 revolutionary Uprising in Egypt. It does so by bringing to focus the relationship between these forces' everyday spatial practices and forms of contention, on one hand, and revolutionary activism and protests in central places like Tahrir Square, on the other. It demonstrates that everyday life in popular neighbourhoods of Cairo is constitutive of a political domain in which ordinary citizens cultivate resources, dispositions and capacities for collective action and mobilisation of the kind witnessed in the January Uprising. It also shows how the lived experiences of ordinary citizens in the city's popular neighbourhoods are formative of the oppositional subjectivities enacted in the context of this revolutionary mobilisation. The article identifies and illuminates two primary paradoxes of revolutionary mobilisation. The two paradoxes arise out of a disjuncture between modalities of action pursued by Tahrir-oriented revolutionary activists ( al-thuwwar ) on one hand, and popular forces' tactics, strategies and conception of the Revolution, on the other. Tracing the engagement of popular forces in the context of the Uprising, this contribution reveals that in enacting their oppositional subjectivities popular forces articulated their own conception of the Revolution. More specifically, the article expounds on how they did so by shifting the locale of revolutionary action from Tahrir Square to Cairo's streets and popular neighbourhoods, and by widening acts of urban insurgency to advance rights claims to the city.